PHYTOTHERAPY USED IN AFRO-INDEGENUOS COMMUNITIES FOR ANIMALS AND PEOPLE: fitoterapia utilizada em comunidades afro-indígenas para animais e pessoas - Costa, Daniel de Azevedo Silva; Virgínio, Sérgio Ricardo de Andrade; Roberto, João Vinicius Barbosa; FERREIRA, MARIA DAS GRAÇAS NOGUEIRA; Batista, Álisson Fernando Soares; Cordão, Maiza Araújo (Revista de Ciências da Saúde Nova Esperança, 2025)
Ethnobotany is the ethnographic study of plants and herbs passed down through the oral tradition of a particular ethnic group. The African Brazilian religion, Candomblé, keeps and transmits medicinal knowledge in its practices, such as the use of herbs and plants, which, in their biochemical context, are effective against various clinical pathologies. With the growth of the pharmaceutical industry, science is also expanding its research into new drugs and options for medicinal treatment, thus giving rise to herbal medicine. In addition to reducing economic costs, as it is an abundant raw material, i.e., widely present even in people's backyards, herbal medicine provides a variety of effective therapeutic options for treating pathologies. The aim of this study was to identify the medicinal herbal knowledge used in some African-Brazilian communities in João Pessoa-PB. Interviews were carried out, using a questionnaire, with babalorixás and yalorixás from the municipality. The information collected from the religious leaders revealed a wide range of knowledge, such as the use of O. basilicum (basil) to treat colic in newborn children, respiratory and stomach problems. The herbal knowledge of the African community's religious leaders is wide-ranging and applicable to the treatment of various pathologies. 100% of the priests claimed to have used herbs and plants to treat children of the house, and 80% of the priests to treat non-human animals. Some of the herbs and plants mentioned were: thorny pigweed, wild sage, skunkweed, American wormseed, Brazilian peppertree, cow-foot leaf, aloe vera, peppermint, myrrh, boldo, rosemary, and basil. The infectious diseases treated were gastrointestinal, pain, wounds, and even more complex infections such as pneumonia.